Evaluation of antibacterial activity and toxicity of licuala spinosa stems / Nurul Ariffah Othman - Othman, Nurul Ariffah (Faculty of Applied Sciences, 2014)
Medicinal plants have many traditional claims including the treatment of ailments of infectious origin. In the evaluation of traditional claims, scientific research is important. The objective of the study was to evaluate the antibacterial activity of methanol extract of Licuala spinosa stems and to evaluate the acute toxicity of methanol extract of Licuala spinosa stems. In this preliminary investigation, the extract was prepared through maceration of dried powdered stems of the plant by methanolic solution. The antibacterial activity of the crude methanol extracts was evaluated at eight different concentrations and subjected to screening against four strains of bacteria species, Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis, and Micrococcus luteus, using standard protocol of disc diffusion method. The methanol extracts was more active against Gram-positive bacteria as compared to Gram-negative bacteria. The antibacterial activities were assessed by the presence or absence of inhibition zones. The inhibitory effect of the extract was compared with standard antibiotic, vancomycin (positive control). The methanol extract of Licuala spinosa stems do not demonstrate any significant antibacterial activity compared with the negative control (p > 0.05). The plant extracts tested showed no antibacterial activities against all four bacterial that were used. Further study of this plant extracts has been tested for acute toxicity in Artemia salina. Methano 1 extracts from Licuala spinosa stems was screened by the brine shrimp lethality assay and found that the extract showed significant toxicity to the brine shrimp. Licuala spinosa stems extract have exhibited potent activity with LC50 38.9 μg/ml.